Enhancing Public Service Delivery in Nigeria Through Agile Practice - Foluso Modupe Adeyinka; Adeyinka Patrick Adewumi (Universitas Medan Area, 2023)
The dynamic nature of today's public sector demands innovative approaches to service delivery, leading to the emergence of agility as a vital paradigm. This research investigates the transformative potential of agile methodologies in restructuring the Nigerian public sector for enhanced service delivery. Emphasizing the need for agility in response to technological advancements and global shifts, the study draws on Nigeria's digital policy frameworks, such as the Nigeria e-Government Interoperability Framework (Ne-GIF) and the National Digital Economy Policy and Strategy (NDEPS) 2020-2030. The research advocates a shift from traditional bureaucratic structures to a more integrated, networked approach that prioritizes citizen participation and fosters service-centric cultures. The study uses a qualitative approach to gather secondary data from diverse sources and employs thematic and content analysis. The findings reveal that agile methodologies have the potential to reshape the Nigerian public sector.